Pengolahan Limbah Tekstil Menggunakan Elektrokoagulasi - Tuani Lidiawati S (Seminar Nasional Teknik Kimia Kejuangan, 2015)
The study investigates the influence of operating parameters such as initial pH and distance between electrode on COD and color removal from a laboratory scale batch electrocoagulation reactor using aluminum plate (Al) with a broad cross section of 80x80 mm2 and 2 mm thick as the electrode. Synthetic wastewater Direc Red 12 B® and Direc Black Ex® is used in the study with a volume of 800 mL. The variations of experiments are distance between electrodes (2 cm, 3 cm and 4 cm) and the initial pH (4, 5, 6,7). The samples are taken every 5 minutes for 60 minutes operating time. The results of the study indicate that electrocoagulation optimal condition occurs at electrode distance 2 cm and initial pH 5 with the color removal efficiency 94.5% of the Direc Red 12 B® and 98.3% of Black Direc Ex®, COD removal 91.25% of Direc Red 12 B® and 84.92% of Direc Black Ex®.